Causing or inciting sexual activity with persons who have a mental disorder. (25th November 2021) - Griffith, Richard
Abstract : Richard Griffith, Senior Lecturer in Health Law at Swansea University, discusses the implications of a Court of Appeal decision that considers the scope of the Sexual Offences Act 2003, section 39, in relation to care workers